2021
DOI: 10.3934/microbiol.2021025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan nanoparticles on quorum sensing-controlled virulence factors and expression of <i>LasI</i> and <i>RhlI</i> genes among <i>Pseudomonas aeruginosa</i> clinical isolates

Abstract: <abstract> <p>Antibiotic-resistant strains of <italic>Pseudomonas aeruginosa (P. aeruginosa</italic>) pose a major threat for healthcare-associated and community-acquired infections. <italic>P. aeruginosa</italic> is recognized as an opportunistic pathogen using quorum sensing (QS) system to regulate the expression of virulence factors and biofilm development. Thus, meddling with the QS system would give alternate methods of controlling the pathogenicity. This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[ 244 ] Besides the lack of in‐vivo studies, most studies have only confirmed at the phenomenological level that nanomaterials have QS regulatory effects (such as reducing the production of QS‐regulated virulence factors, inhibiting swarming and swimming motility, and disrupting biofilm formation), while research on the specific molecular mechanisms by which nanomaterials regulate bacterial QS is relatively limited. [ 245 ] The possible reason is that existing mechanistic research mostly relies on computerized molecular docking techniques to simply predict whether there is a direct interaction between nanomaterials and known QS system components. [ 150 , 246 ] The introduction of more advanced analytical tools in the future, such as high‐resolution single‐atom imaging techniques, is expected to break through this limitation.…”
Section: Limitations and Prospectsmentioning
confidence: 99%
“…[ 244 ] Besides the lack of in‐vivo studies, most studies have only confirmed at the phenomenological level that nanomaterials have QS regulatory effects (such as reducing the production of QS‐regulated virulence factors, inhibiting swarming and swimming motility, and disrupting biofilm formation), while research on the specific molecular mechanisms by which nanomaterials regulate bacterial QS is relatively limited. [ 245 ] The possible reason is that existing mechanistic research mostly relies on computerized molecular docking techniques to simply predict whether there is a direct interaction between nanomaterials and known QS system components. [ 150 , 246 ] The introduction of more advanced analytical tools in the future, such as high‐resolution single‐atom imaging techniques, is expected to break through this limitation.…”
Section: Limitations and Prospectsmentioning
confidence: 99%
“…This can lead to the formation of an impermeable layer of CS-NPs around the bacterium, thereby preventing transport through the outer membrane of G-bacteria. 10 Additionally, the nanoscale dimensions may promote biocompatibility and reduce unwanted interactions with the immune system. 11 As a result, we have embarked on an investigation into the antimicrobial effects of CS-NPs using a model microorganism for biofilm formation, Pseudomonas aeruginosa (PA).…”
Section: Introductionmentioning
confidence: 99%